Age Variance in the Survival of United States Pediatric Leukemia Patients (1973–2006). (6th August 2012) - Holmes, L.; Opara, F.; Des-Vignes-Kendrick, M.; Hossain, J.
Abstract : Background . Age at diagnosis remains an important prognostic factor in pediatric leukemia. However, it is not fully understood which prognostic factors are related to its effect on survival. This study aimed to assess the effect of age at diagnosis on pediatric leukemia survival in the United States (US). Methods . We utilized the Surveillance Epidemiology and End Results (SEER) data of the diagnosed pediatric leukemia patients (n = 15215 ) from 1973–2006. Life table, Kaplan-Meier, log rank test, and Cox proportional hazard methods were used to examine the data. Results . The overall 5-year survival was 67.9%. Infants and children of 18 and 19 years had the highest risk of dying, with a rapid declining risk of death at age of 1 year that continued until age of 3 years and thereafter a steady trend of increased risk of death. The increased risk of dying was associated with boys, T-cell type and more than one primary tumor, P < 0.0001. There was significant variability in survival by the age group at diagnosis. Compared to age group <1 year, children of ages 1–4 years, 5–9 years, 10–14 years, and 15–19 years were 76% (adjusted hazard ratio (AHR) = 0.24, 99% CI = 0.21–0.28), 69% (AHR = 0.31, 99% CI = 0.26–0.36), 46% (AHR = 0.54, 99% CI = 0.46–0.62), and 18% (AHR = 0.82, 99% CI = 0.70–0.95) less likely to die, respectively. Conclusion . The age at tumor diagnosis was a single most potent prognostic factor of childhood leukemia survival, with infants and children of age group 15–19 years experiencing the poorest survival. This significant variability persisted after adjustment for the effect of other covariates. Therefore, there is a need to identify other prognostic factors that are associated with age in order to provide a meaningful explanation of the impact of age on pediatric leukemia survival in the US.